What is more important: defibrillation or compression? - Gu, Wei; Li, Chun-Sheng (Journal of Thoracic Disease, 2016)
Cardiac arrest (CA) is one of the leading causes of death and is responsible for approximately 400,000 deaths per year in the United States (1). A recent investigation (American Heart Association) showed that more than 200,000 inpatients had CA in 2013 in the United States (2). China has approximately 540,000 deaths from CA each year, ranking first in the world. However, the success rate of rescue for CA is extremely low and the success rate of prehospital resuscitation for patients with CA is only 4.2% in the capital of China, Beijing (medically developed area) (3).